2007
DOI: 10.1093/aje/kwm342
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Thyroid Autoantibodies during the Third Trimester and Hearing Deficits in Children: An Epidemiologic Assessment

Abstract: Elevated maternal thyroid autoantibodies during pregnancy are linked to infertility, miscarriage, and neurodevelopmental deficits such as in cognitive function. It has not been established whether autoantibodies to thyroid peroxidase are associated with sensorineural hearing loss (SNHL). The authors tested stored third-trimester maternal serum specimens of 1,736 children for thyroid peroxidase autoantibodies (TPOaAb) by using an enzyme-linked immunosorbent assay technique. The children participated at the Balt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 66 publications
1
29
0
3
Order By: Relevance
“…After screening the titles and abstracts, 22 studies were further assessed for eligibility by reading full-text [12][13][14][15][16][17][18][19]. After reviewing full-text, 15 articles were excluded because of not relevant design or lack of usable data [12,[23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Thus, seven prospective cohort studies were finally included into the metaanalysis [13][14][15][16][17][18][19].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…After screening the titles and abstracts, 22 studies were further assessed for eligibility by reading full-text [12][13][14][15][16][17][18][19]. After reviewing full-text, 15 articles were excluded because of not relevant design or lack of usable data [12,[23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Thus, seven prospective cohort studies were finally included into the metaanalysis [13][14][15][16][17][18][19].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…16) in term infants, to CP, 48 to decreased IQ, 51 and to congenital deafness. 52 Antithyroid antibodies are present in 10% of pregnancies 53 and 10% of neonates. 54 No study has sought to examine further the possibility that thyroid hormone level or presence of antithyroid antibodies contributes importantly to encephalopathy in term neonates or to CP, although if present these associations would suggest potential therapeutic interventions.…”
Section: Clues Not Pursuedmentioning
confidence: 99%
“…We previously observed that TPOaAb elevation in women during the third trimester of pregnancy was strongly (prevalence odds ratio 7.5) and significantly (95% confidence interval: 2.4, 23.3) associated with sensorineural hearing loss (SNHL) in their children (14). The strength of the association became more robust as the TPOaAb concentration increased, even in women who were clinically euthyroid.…”
mentioning
confidence: 97%